Cathepsin K Deficiency Prevented Kidney Damage and Dysfunction in Response to 5/6 Nephrectomy Injury in Mice With or Without Chronic Stress. Issue 8 (21st June 2022) - Yue, Xueling; Piao, Limei; Wang, Hailong; Huang, Zhe; Meng, Xiangkun; Sasaki, Takeshi; Inoue, Aiko; Nakamura, Kae; Wan, Ying; Xu, Shengnan; Shi, Guo-Ping; Kim, Weon; et al.
Abstract : Background: Chronic psychological stress is a risk factor for kidney disease, including kidney dysfunction and hypertension. Lysosomal CatK (cathepsin K) participates in various human pathobiologies. We investigated the role of CatK in kidney remodeling and hypertension in response to 5/6 nephrectomy injury in mice with or without chronic stress. Methods: Male 7-week-old WT (wild type; CatK +/+ ) and CatK-deficient (CatK −/− ) mice that were or were not subjected to chronic stress underwent 5/6 nephrectomy. At 8 weeks post-stress/surgery, the stress was observed to have accelerated injury-induced glomerulosclerosis, proteinuria, and blood pressure elevation. Results: Compared with the nonstressed mice, the stressed mice showed increased levels of TLR (Toll-like receptor)-2/4, p22 phox, gp91 phox, CatK, MMP (matrix metalloproteinase)-2/9, collagen type I and III genes, PPAR-γ (peroxisome proliferator-activated receptor-gamma), NLRP-3 (NOD-like receptor thermal protein domain associated protein 3), p21, p16, and cleaved caspase-8 proteins, podocyte foot process effacement, macrophage accumulation, apoptosis, and decreased levels of Bcl-2 (B cell lymphoma 2) and Sirt1, as well as decreased glomerular desmin expression in the kidneys. These harmful changes were retarded by the genetic or pharmacological inhibition of CatK. Consistently, CatK inhibition ameliorated 5/6 nephrectomy–related kidney injury and dysfunction. In mesangial cells, CatK silencing or overexpression, respectively, reduced or increased the PPAR-γ and cleaved caspase-8 protein levels, providing evidence and a mechanistic explanation of CatK's involvement in PPAR-γ/caspase-8–mediated cell apoptosis in response to superoxide and stressed serum. Conclusions: These results demonstrate that CatK plays an essential role in kidney remodeling and hypertension in response to 5/6 nephrectomy or stress, possibly via a reduction of glomerular inflammation, apoptosis, and fibrosis, suggesting a novel therapeutic strategy for controlling kidney injury in mice under chronic psychological stress conditions.